Correlation of Central Corneal Thickness with Refractive Error, Corneal Curvature, and Axial Length: An Observational Study - Chinthala Navyasree; Jasmita Satapathy (TNOA Journal of Ophthalmic Science and Research, 2024)
Background: Various demographic and ocular factors influence central corneal thickness (CCT). Studies on the relationships between these parameters have shown conflicting results. We aim to investigate the correlation of CCT with different types of refractive error, axial length (AL), and corneal curvature. Materials and Methods: An observational study was undertaken in the Department of Ophthalmology, recruiting patients from 18 to 40 years of age with myopia (−0.5 D to −6 D) or hypermetropia (≤ +3 D) or emmetropia (−0.25 D to +0.25 D). All participants underwent comprehensive ophthalmic examination, including refraction, slit lamp examination and fundoscopy, followed by CCT, corneal curvature, and AL measurement. Result: A total of 1224 eyes of 612 patients (260 males and 352 females) were enrolled in the study. Out of them, 31.5% (n = 386) had emmetropia, 28.6% (n = 350) had hypermetropia, and 39.9% (n = 488) had myopia. The mean (±standard deviation [SD]) keratometry (K), CCT and AL were found to be 44.08 (±1.55) D, 528.46 (±29.78) μm, and 22.75 (±1.21) mm, respectively. With increasing age, CCT was found to be decreased (P < 0.001). Compared to myopia, a significantly higher CCT was noted in hypermetropia (P < 0.001). There was a negative correlation between CCT and corneal curvature among the entire study population, irrespective of their refractive status (P < 0.001). This correlation was more significant among emmetropes and hypermetropes as compared to myopes. However, we found no correlation between CCT and AL in any groups. Conclusion: CCT is found to be thicker in hypermetropia and thinner in myopia as compared to emmetropia. With increasing age, the cornea tends to become steeper and thinner.